Selection of an Appropriate Biomass Burner for Drying Maize in a Crossflow Column Dryer Using an Analytic Hierarchy Process - George Obeng-Akrofi; Joseph Oppong Akowuah; Dirk E. Maier; Ahmad Addo (Green Engineering Society, 2022)
Several post-harvest technologies have been introduced over the past years to help smallholder farmers in sub-Saharan Africa reduce crop losses. However, not all these technologies fit the same application purpose to meet the needs of farmers in different locations. This study, therefore, applied a multi-criteria decision method, the analytical hierarchy process (AHP), to select an appropriate biomass burner based on its technical performance, cost, and design criteria to complete the setup of a low-cost column dryer. With a priority value of 0.69 out of 1.00, the KNUST-ABE Biomass Burner was selected over the AFLASTOP Biomass Burner which had a priority value of 0.31 out of 1.00. Based on the results of this study, the AHP multi-criteria decision method was helpful in the selection of a locally developed biomass burner for a low-cost column drying system.